Growth and developments in Islamic social finance sector: maqasid-driven microfinancing innovations in Islamic social finance for B-40 empowerment - Busari, Saheed Abdullahi (Cambridge Institute of Islamic Finance, 2026)
This chapter explores how maqasid al-Shari’a can drive innovative microfinancing solutions within Islamic social finance to enhance the socio-economic empowerment of B40 households in Malaysia. While Islamic social finance, anchored in zakat, waqf, qard al-hasan and sadaqa, has grown significantly, gaps remain in achieving long-term financial inclusion, livelihood sustainability and upward mobility among low-income groups. Many microfinance initiatives operate in silos or emphasise financing access without integrating broader maqasid principles such as the preservation of life, intellect, wealth and human dignity. This chapter conducts a conceptual and analytical review of contemporary literature and practices to propose a maqasid-based microfinancing model that aligns ethical objectives with inclusive development outcomes. Key innovations include blended waqf-microfinance instruments, integrated zakat-based social protection pathways, digital microfinancing platforms, and maqasid-linked performance indicators. These innovations are assessed for their ability to generate holistic empowerment, reduce financial vulnerability and support resilient income pathways for the B40. The chapter concludes by offering policy recommendations to strengthen Islamic social finance institutions and enhance their developmental impact through maqasid-driven strategies.